A new genus and species of Rhopalidae (Hemiptera: Heteroptera) from the Early Cretaceous of Liaoning Province, China - Chen, Xiaotong; Yao, Yunzhi; Ren, Dong (Zootaxa, 2015)
A new fossil Vescisalignus indecorus gen. et sp. nov. (Rhopalidae) is described and illustrated from the Early Cretaceous. All the specimens described here were collected from the Yixian Formantion of Beipiao City, Liaoning Province, northeastern China. This is the first report of rhopalid from Yixian Formation in Liaoning Province, China.